2018
DOI: 10.1136/bmjopen-2017-020196
|View full text |Cite
|
Sign up to set email alerts
|

Common mental disorders among Indigenous people living in regional, remote and metropolitan Australia: a cross-sectional study

Abstract: ObjectiveTo determine, using face-to-face diagnostic interviews, the prevalence of common mental disorders (CMD) in a cohort of adult Indigenous Australians, the cultural acceptability of the interviews, the rates of comorbid CMD and concordance with psychiatrists’ diagnoses.DesignCross-sectional study July 2014–November 2016. Psychologists conducted Structured Clinical Interviews for Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision Axis I Disorders (SCID-I) (n=544). Psychia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 26 publications
2
68
0
Order By: Relevance
“…mood, anxiety, and substance use including alcohol) among Indigenous Australians was up to 6.9 times higher than those of the Australian population [33], for Indigenous Australians living on traditional lands and in remote areas the rate of common mental disorders was half compared to those living in major cities or regional areas [33]. This suggests that connection to their traditional lands and communities is an important determinant of their mental health [33]. Although there has been some success in the reduction of harmful alcohol consumption among Indigenous communities [30], more needs to be done to prevent and minimise alcohol-related harm among individuals who consume alcohol.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…mood, anxiety, and substance use including alcohol) among Indigenous Australians was up to 6.9 times higher than those of the Australian population [33], for Indigenous Australians living on traditional lands and in remote areas the rate of common mental disorders was half compared to those living in major cities or regional areas [33]. This suggests that connection to their traditional lands and communities is an important determinant of their mental health [33]. Although there has been some success in the reduction of harmful alcohol consumption among Indigenous communities [30], more needs to be done to prevent and minimise alcohol-related harm among individuals who consume alcohol.…”
Section: Discussionmentioning
confidence: 87%
“…A study conducted in Queensland and New South Wales has shown that while the rate of common mental disorders (e.g. mood, anxiety, and substance use including alcohol) among Indigenous Australians was up to 6.9 times higher than those of the Australian population [33], for Indigenous Australians living on traditional lands and in remote areas the rate of common mental disorders was half compared to those living in major cities or regional areas [33]. This suggests that connection to their traditional lands and communities is an important determinant of their mental health [33].…”
Section: Discussionmentioning
confidence: 99%
“…The 20-year difference in mean age at death between Indigenous and non-Indigenous Australians in this study is the largest we have observed. Furthermore, we have recently found that the rate of current common mental disorders among Indigenous Australians is 4.2-times higher than that of the general Australian population (Nasir et al, 2018). Comorbid mental disorder was 3-to 4-times higher.…”
Section: Discussionmentioning
confidence: 87%
“…For instance, Indigenous Australians and New Zealanders report less psychiatric morbidity when they form a higher proportion of the population despite other markers of social deprivation, possibly because of connection to culture and traditional lands. 7,8 Elsewhere, a Canadian survey found that 70% of First Nations adults living on reserves felt in balance physically, emotionally, mentally and spiritually. 9 Indigenous people may therefore have higher rates of psychological distress because of factors unrelated to ethnicity, but experience lower rates of disorders because of cultural connection or density.…”
Section: Indigenous Peoples Of North Americamentioning
confidence: 99%
“…Sidharth Arya, 1 Mirjana Delic, 2 Blanca Iciar Indave Ruiz, 3 Jan Klimas, 4 Duccio Papanti, 5 Anton Stepanov, 6 Victoria Cock 7 and Dzmitry Krupchanka 8…”
Section: Closing the Gap Between Training Needs And Training Provisiomentioning
confidence: 99%